Neuroscience in Islamic Education: A Systematic Review of Implications for Memorization, Devotion, and Faith - Samsiroh, Samsiroh; Aliyah, Nelud Darajaatul; Hariani, Mila (Journal of Social Science Studies, 2024)
The convergence between neuroscience and religious education opens up new perspectives for improving the effectiveness of Islamic Religious Education (IRE). This academic paper, based on a literature review, conducts a systematic review to analyse the implications of neuroscience findings on three main domains of IRE: memorisation of the Qur’an, concentration in worship, and strengthening of faith. The study uses a qualitative approach with a thematic synthesis method of relevant scientific literature. The results show that neuroscience concepts such as neuroplasticity and memory consolidation provide a strong foundation for refining the tahfiz methodology with material breakdown and spaced repetition techniques. Findings on attention regulation and the Default Mode Network identify that devotion can be trained through strategies to strengthen focus and reduce wandering thoughts. Meanwhile, understanding the mechanisms of belief formation emphasises the importance of an approach to teaching faith that integrates narrative, emotional experience, and practical application for deeper internalisation of values. This paper concludes that the integration of neuroscience into Islamic Education has the potential to produce more evidence-based, humane learning methods that have an impact on cognitive and affective levels. Its implementation requires curriculum adjustments, teacher training, and the transformation of learning management in Islamic educational institutions.